The Influence of Social Media Addiction to Employees Performance with Cyberloafing as Intervening Variable (Study on Generation Y Workers at MNC) - Rahel Moningkey; Rosaly Franksiska (Universitas Pendidikan Ganesha, 2020)
The use of internet especially social media was inevitable in today’s society. Using the internet effectively and in moderation can become a useful to get the job done efficiently. Inappropriate use of internet or social media can lead to lower performance, particularly if it had become an addiction. The purpose of this research was to test whether social media addiction influence performance with cyber loafing as intervening variable. This was a quantitative research with sample of 110 generation Y workers at MNC in Jakarta. The analysis technique used is path analysis. The result of this research showed that social media addiction is low, with moderate cyberloafing and high performance. The path analysis indicated that social media addiction positively influence cyberloafing, but social media addiction and cyberloafing did not influence employees’ performance. Therefore, Cyberloafing did not act as intervening variable. Different companies have different policies concerning the use of internet. Some company have a strict rule and demands their employees to be professional in a way to did not use their Mobile phone to access their social media or not to cater to their personal need during their working hours. Professionalism is needed by employees to survive in their job. The company demand to be as professional as employees can make them did not addict to their social media. So causes the result of this study that said there is no influence between cyberloafing a social media addiction toward employees’ performance.